Do perceived zakat institutions and government support affect entrepreneurs' intention to pay zakat? - Heri Sudarsono; Indri Supriani; Andika Ridha Ayu Perdana (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – This study aims to determine the effect of attitudes, subjective norms, institutional zakat systems, and government support in influencing the interest of entrepreneurs in paying zakat. Methodology – There are 140 respondents in this research from 6 big cities in Java, such as Jakarta, Serang, Bandung, Semarang, Yogyakarta, and Surabaya. This research uses the Partial Least-Square-Structural Equation Modeling (PLS-SEM) analysis technique with the Theory of Reasoned Action (TRA) model. Finding – The findings reveal that attitudes, subjective norms, and perceived zakat institutions affect entrepreneurs' interest in paying zakat. Meanwhile, perceived government support does not affect entrepreneurs to pay zakat.Implications – Zakat institutions need to regularly involve Muslim entrepreneur organizations in zakat management programs so that perceptions about zakat institutions and the role of government in improving zakat management can increase the motivation of entrepreneurs to pay zakat.Originality – There has been no previous research including perceived zakat institutions and perceived government support as variables influencing entrepreneurs' intention to pay zakat in Indonesia.